Impacts of the music festival Lovefest on the attitudes of the local population in Vrnjacka Banja - Đorđević, Nataša; Podovac, Milena; Milićević, Snežana; Stojanović, Đorđe (Hotel and Tourism Management, 2021)
The electronic music festival Lovefest, which has been held in Vrnjacka Banja since 2007, gathers a great number of domestic and international visitors. In addition to the positive impacts, which are primarily reflected in the generation of income that is important for the tourism economy and to the local population of Vrnja?ka Banja, this event creates numerous negative impacts as well. The purpose of this study is to examine the differences in the local population‘s attitudes to the positive and the negative impacts of Lovefest based on their age, gender, educational level, occupation, and the relation between their job and tourism. To process the primary data descriptive statistical analysis, t-test, and ANOVA are used. The results indicate that the local population‘s attitudes to some positive and negative impacts of Lovefest differ regarding their socio-demographic characteristics.